2011
DOI: 10.1093/jxb/err205
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the microRNAs in superior and inferior spikelets in rice (Oryza sativa)

Abstract: MicroRNAs (miRNAs) play a critical role in post-transcriptional gene regulation and have been shown to control many genes involved in various biological and metabolic processes. This work investigated miRNAs in rice (Oryza sativa), an important food crop. High-throughput sequencing technology was used to reveal expression differences in miRNAs between superior and inferior spikelets in rice (japonica cultivar Xinfeng 2) at 18 d after fertilization. Totals of 351 and 312 known miRNAs were obtained from the supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 48 publications
10
88
3
Order By: Relevance
“…We collected 10 panicles from each plot at 5, 10, 15, 20, 30, and 40 days after heading (DAH) for all three cultivars, as well as at 50 DAH for Takanari. After oven-drying at 80 • C for 72 h, SS and IS samples were collected according to the method of Peng et al (2011). Namely, the 3rd, 4th and 5th spikelets from the tip of the top two rachis branches were collected as SS, whereas the 1st and 2nd spikelets from the base of two secondary rachis branches attached to the 2nd and 3rd primary rachis branches from the neck node were sampled as IS.…”
Section: Harvesting Sampling and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We collected 10 panicles from each plot at 5, 10, 15, 20, 30, and 40 days after heading (DAH) for all three cultivars, as well as at 50 DAH for Takanari. After oven-drying at 80 • C for 72 h, SS and IS samples were collected according to the method of Peng et al (2011). Namely, the 3rd, 4th and 5th spikelets from the tip of the top two rachis branches were collected as SS, whereas the 1st and 2nd spikelets from the base of two secondary rachis branches attached to the 2nd and 3rd primary rachis branches from the neck node were sampled as IS.…”
Section: Harvesting Sampling and Analysismentioning
confidence: 99%
“…Flowering of an entire panicle takes normally from 4 to 7 days, and the early-flowering spikelets located on primary branches at the top of the panicle are referred to as superior spikelets (SS), whereas the late-flowering spikelets located on secondary branches of the lower primary branches are called as inferior spikelets (IS) (Yang and Zhang, 2010;Peng et al, 2011). The different timing of flowering and thereby grain filling leads to great variation in the weight and quality of SS and IS grains (Matsue et al, 1994;Liu et al, 2005;Cheng et al, 2007;Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the miRNA levels are usually higher than their corresponding miRNA*. However, a recent study in plants proved that both miRNA and miRNA* can silence different targets [37,38], and ample studies have shown that miRNA*s can have a higher expression level than their miRNAs in plants [9,35,39]. Here, we also encountered similar situations; in our datasets, six miRNA*s (miR160a*, miR164b*, miR169b*, miR395f*, miR396a*, and miR5225*) are expressed at a higher level than their corresponding miRNAs (Supplementary Fig.…”
Section: Identification Of Conserved Mirnas In P Dactyliferamentioning
confidence: 99%
“…To investigate the expression patterns of miRNAs among the six different stages of fruit development and ripening, the read count of each expressed miRNA was normalized to transcripts per million (TPM) using the following formula: normalized expression = actual read count / total read count × 1,000,000 [39]. After normalization, the expression was set to 0.01 for miRNAs that are not expressed.…”
Section: Differential Expression and Quantitative Real Time Rt-pcr Anmentioning
confidence: 99%
“…Within a panicle, the superior spikelets can inhibit the inferiors, and this apical spikelets superiority of superior spikelets over inferior spikelets can partly be demonstrated by application of the exogenous auxin (IAA) (Wang et al, 2001, 2003). Furthermore, different expressions and functions of miRNAs exist between the superior and inferior spikelets (Peng et al, 2011, 2014). The interaction among the factors inside spikelets, including the hormones, mRNA transcriptions, protein expressions, and activities of key enzymes involved in sucrose-to-starch conversion, regulate the grain-filling process of superior and inferior spikelets (Yang et al, 2006; Zhang et al, 2009; Yang and Zhang, 2010).…”
Section: Introductionmentioning
confidence: 99%